Dividend policy and performance of listed firms on Ghana stock exchange - Ahmed Bossman; Samuel Kwaku Agyei; Oliver Asiamah; Ellen Animah Agyei; Emmanuel Yaw Arhin; Edward Marfo-Yiadom (Cogent Economics & Finance, 2022)
We examined the dividend policy and financial performance nexus among listed firms in Ghana, having controlled for firm age, size, capital structure, governance, and financial sector clean-up. We employed the system dynamic general method of moments (GMM) estimation technique with data from 2015 to 2019. In addition to dividend payout, new proxies of dividend policy (dividend capacity and free cash flow savings) were employed to ascertain their impact on firm performance in a period filled with financial sector reforms and clean-ups. We found a significant effect of dividend capacity on Return on Assets and Return on Equity. Free cash flow savings was found to have a direct and significant effect on Return on Assets and Return on Equity but an indirect relationship with both Tobin's Q and stock price. Our findings indicate that while dividend capacity and free cash flow savings are positively connected with firm performance, dividend payout detrimentally affects owners' wealth during crisis periods. The findings divulged a detrimental effect of financial sector clean-ups on the performance of non-financial firms only. It is recommended that corporations maintain a balance between dividend payout and free cash flow savings to attract all classes of investors. Governments and market regulators alike must take practical steps to roll out policies on financial sector reforms and/or clean-ups to mitigate the detrimental impacts of inadvertent reforms and/or clean-ups on other sectors of the economy. Investors, market regulators, and governments seek to benefit from the findings of our study.
Keywords: G1; G34; G35; 330; dividend policy; financial sector clean-up; firm performance; firm value; free cash flow; Ghana stock exchange; GMM